Effort in Low-Stakes Assessments: What Does It Take to Perform as Well as in a High-Stakes Setting? - Attali, Yigal (Educ Psychol Meas, 2016)
Performance of students in low-stakes testing situations has been a concern and focus of recent research. However, researchers who have examined the effect of stakes on performance have not been able to compare low-stakes performance to truly high-stakes performance of the same students. Results of such a comparison are reported in this article. GRE test takers volunteered to take an additional low-stakes test, of either verbal or quantitative reasoning as part of a research study immediately following their operational high-stakes test. Analyses of performance under the high- and low-stakes situations revealed that the level of effort in the low-stakes situation (as measured by the amount of time on task) strongly predicted the stakes effect on performance (difference between test scores in low- and high-stakes situations). Moreover, the stakes effect virtually disappeared for participants who spent at least one-third of the allotted time in the low-stakes situation. For this group of test takers (more than 80% of the total sample), the correlations between the low- and high-stakes scores approached the upper bound possible considering the reliability of the test.